Closed revitalization as an example of post-industrial area management in Łódź - Świerczewska-Pietras, Katarzyna (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2009)
The purpose of this article is to describe and analyze the notion of closed revitalization as an example of function alteration of post-industrial areas’ of I.K. Poznanski factory in Łódź. In Poland, due to the transformation of the system and economy, the country’s entry into the European Community and finally equalization of opportunities and balancing of the differences between our state and the countries of Western Europe, revitalization of degraded urban areas is, currently, more and more often recognized as an important issue. In recent years, several revitalization projects aiming at the alteration of functions of post-industrial areas have been commenced. Non-profitable operation of industrial plants led to a decrease in production and, thus, a decrease in employment. Sizes of the industrial facilities and limited technical possibilities regarding renovation works often did not allow for the development of the facilities by potential lessees. Those locations have stood abandoned and useless for many years, losing their architectural value and contributing to the spatial degradation of their respective city areas. Therefore, the identities of those cities which were strongly associated with industrial production have been gradually lost. Alteration of the functions of such sites by means of revitalization is an opportunity for their prospective development and growth.